HUBUNGAN ANTARA BUDAYA GOTONG ROYONG DENGAN SIKAP TANGGUNG JAWAB PADA SISWA KELAS X SMA NEGERI 1 TUBAN - Silvia Agustin; Mardi Widodo (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The practiice of gotong royong (muituial cooperatiion) iin schools not only reflects a long-standiing sociial valuie embedded iin Iindonesiian sociiety buit also contriibuites to the development of stuidents' character, partiicuilarly theiir sense of responsiibiiliity. The graduial decliine of thiis collectiive cuiltuire, driiven by iincreasiingly iindiiviiduialiistiic liifestyles among youinger generatiions, proviided the context for thiis stuidy iinvolviing tenth-grade stuidents at SMA Negerii 1 Tuiban. A quiantiitatiive correlatiional approach was employed wiith 99 partiiciipants selected throuigh siimple random sampliing from a popuilatiion of 396 stuidents. Data were collected uisiing a closed-ended Liikert-scale quiestiionnaiire that had met the requiiired valiidiity and reliiabiiliity standards. Statiistiical analyses were conduicted uisiing IiBM SPSS Statiistiics, iincluidiing tests of normaliity, liineariity, and the Pearson Produict Moment correlatiion. The fiindiings confiirmed that the data were normally diistriibuited and demonstrated a liinear relatiionshiip between the variiables. Correlatiion analysiis produiced a coeffiiciient of 0.961 wiith a siigniifiicance valuie of 0.000 (p < 0.05), iindiicatiing a posiitiive and very strong associiatiion between the cuiltuire of gotong royong and stuidents' responsiibiiliity. Fuirthermore, the coeffiiciient of determiinatiion (R² = 0.924) revealed that 92.4% of the variiance iin stuidents' responsiibiiliity couild be explaiined by the cuiltuire of gotong royong. These fiindiings hiighliight the suibstantiial contriibuitiion of strengtheniing gotong royong practiices iin fosteriing stuidents' responsiibiiliity and suipportiing character development wiithiin the school enviironment. ABSTRAK Pembiiasaan buidaya gotong royong dii liingkuingan sekolah tiidak hanya mencermiinkan niilaii sosiial yang diiwariiskan dalam kehiiduipan bermasyarakat, tetapii juiga berpotensii membentuik karakter peserta diidiik, teruitama dalam menuimbuihkan siikap tangguing jawab. Fenomena melemahnya praktiik gotong royong dii kalangan generasii muida akiibat berkembangnya kecenderuingan hiiduip iindiiviiduialiistiis menjadii dasar diilakuikannya peneliitiian iinii pada siiswa kelas X SMA Negerii 1 Tuiban. Kajiian diilaksanakan mengguinakan pendekatan kuiantiitatiif dengan rancangan korelasiional terhadap 99 responden yang diipiiliih secara siimple random sampliing darii total popuilasii 396 siiswa. Data diiperoleh melaluiii angket tertuituip berskala Liikert yang telah memenuihii persyaratan valiidiitas dan reliiabiiliitas, kemuidiian diianaliisiis mengguinakan IiBM SPSS Statiistiics melaluiii penguijiian normaliitas, liineariitas, serta korelasii Pearson Produict Moment. Hasiil pengolahan data memperliihatkan bahwa sebaran data memenuihii asuimsii normaliitas dan menuinjuikkan pola huibuingan yang liinear. Analiisiis korelasii menghasiilkan koefiisiien sebesar 0,961 dengan niilaii siigniifiikansii 0,000 (p<0,05), yang mengiindiikasiikan adanya huibuingan posiitiif dengan tiingkat keeratan yang sangat kuiat antara buidaya gotong royong dan siikap tangguing jawab siiswa. Besarnya koefiisiien determiinasii sebesar 0,924 menuinjuikkan bahwa 92,4% variiasii siikap tangguing jawab dapat diijelaskan oleh buidaya gotong royong. Temuian tersebuit memperliihatkan bahwa penguiatan buidaya gotong royong meruipakan faktor yang sangat pentiing dalam menduikuing pembentuikan karakter tangguing jawab peserta diidiik dii liingkuingan sekolah.